Carbohydrate intake and activation of gastric acid secretion decrease gastric estrogen secretion - Takao Ito; Yuichi Ozaki; Atsushi Tanaka; Yoshimitsu Kanai (Scientific Reports)
Abstract Gastric parietal cells (gastric acid-secreting cells) secrete estrogen in response to blood lipid (triglycerides [TG] and fatty acids [FFA]) levels. Since estrogen helps reduce blood lipid levels, gastric estrogen would be important in lowering elevated blood lipid levels. However, gastric parietal cells use lipid-derived energy for estrogen production and acid secretion. Thus, postprandial changes in blood lipid levels and acid secretion could affect gastric estrogen production. Here, we show that blood estrogen and FFA decrease after meals, especially after carbohydrate intake. Postprandially decreased blood estrogen levels are partially restored by intravenous lipid injections. Hormones that activate and suppress gastric acid secretion decrease and increase estrogen production in isolated gastric gland epithelia, respectively. Suppression of gastric acid secretion increases blood estrogen levels in postprandial, but not in fasted, rats. Carbohydrate ingestion releases insulin, which lowers blood FFA levels, while lipid intake releases hormones that suppress gastric acid secretion, such as glucagon-like peptide-1 (GLP-1). Insulin and gastric estrogen directly enter the liver in high concentrations, enhancing and suppressing hepatic de novo lipogenesis, respectively. The more lipids ingested, the less lipogenesis is required. Therefore, we propose that ingested carbohydrates and lipids negatively and positively control gastric estrogen production, respectively, for proper hepatic lipogenesis.